2008
DOI: 10.1002/ppap.200800041
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Barrier Coatings from Vinyltrimethylsilane‐Fed Glow Discharges

Abstract: Radio‐frequency glow discharges fed with vinyltrimethylsilane have been studied for the deposition of barrier coatings onto polymer substrates as single or multiple layers. The deposition process has been investigated considering both the chemistry of the coatings and the spectroscopic analysis of the gas phase. It has been shown that RF power and oxygen addition allow one to switch from organosilane films to silica‐like inorganic, dense, barrier films. A deposition mechanism is suggested for the interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The best values reported here are obtained without any precleaning measures taken to minimize the particle or defects on the polymer substrate. These very low barrier values for single layer SiO 2 ‐like films, to the authors knowledge, have never been achieved from either well established low pressure4, 7, 33, 34 or emerging high pressure plasma technologies 35, 36. The intrinsic high‐quality of the layers; i.e., adhesion, smoothness, uniformity, purity, packing density and low level of surface defects comparable to the uncoated polymer surface may all contribute to the enhanced barrier properties.…”
Section: Resultsmentioning
confidence: 85%
“…The best values reported here are obtained without any precleaning measures taken to minimize the particle or defects on the polymer substrate. These very low barrier values for single layer SiO 2 ‐like films, to the authors knowledge, have never been achieved from either well established low pressure4, 7, 33, 34 or emerging high pressure plasma technologies 35, 36. The intrinsic high‐quality of the layers; i.e., adhesion, smoothness, uniformity, purity, packing density and low level of surface defects comparable to the uncoated polymer surface may all contribute to the enhanced barrier properties.…”
Section: Resultsmentioning
confidence: 85%
“…For each system a single SiO 2 layer was deposited as a reference. The 100-nm-thick SiO 2 layer shows already very good effective barrier properties, with an average barrier improvement factor (BIF) of 80 with respect to the pristine PEN substrate, superior to other values reported in literature for PE-CVD deposited SiO 2 layers [16,19,50]. When two 100-nm-thick SiO 2 layers are coupled with a 200-nmthick poly(V 3 D 3 ) layer, the barrier property of the multilayer further improves, with an overall BIF with respect to the pristine PEN of 1000.…”
Section: Effective Barrier Performancementioning
confidence: 65%
“…Additionally, different deposition approaches such as atomic layer deposition (ALD) in combination with molecular layer deposition [10][11][12][13][14], and all PE-CVD developed multilayers have been reported in literature [15][16][17][18]. Coclite et al [19] reported on the deposition of multilayers based on organosilicon chemistry, in which the inorganic barrier layer is deposited by means of PE-CVD and the organic interlayer is deposited by means of initiated-CVD (i-CVD) [20][21][22].…”
Section: Introductionmentioning
confidence: 97%
“…Low monomer depletions can be ascribed to the high pressure and low power, which result in low‐energy electron collisions and in turn low fragmentation and in formation of heavy “structure‐retaining” fragments. Also the lack of the oxygen in the gas feed, which would enhance the monomer fragmentation in low power discharges, contributes to reduce the reaction pathways in the organic glow discharges 30. In the modulated plasmas, the maximum monomer fragmentation is achieved at DC = 35% and then remains constant for DC > 35% as shown in Figure 8b.…”
Section: Resultsmentioning
confidence: 99%